Resource pulses affect prey selection and reduce dietary diversity of dingoes in arid Australia. (30th May 2019) - Tatler, Jack; Prowse, Thomas A. A.; Roshier, David A.; Allen, Benjamin L.; Cassey, Phillip
Abstract: In Australia, the dingo Canis lupus dingo is the largest terrestrial predator. Dingoes contribute to ecological processes and functions throughout their continental geographic range. Their generalist diet enables daily energetic requirements to be met even in the resource‐limited deserts of central Australia, where irregular rainfall drives extreme fluctuations in mammal assemblages. Given that predation is a primary driver of declining mammal populations and failed reintroductions, it is necessary to understand the dietary intake of the continent's apex predator if conservation outcomes are to be achieved. We performed a meta‐analysis of the mammalian composition of the dingo's diet throughout Australia's arid zone, an area covering c. 5.4 million km 2 . We used 25 data sets from 11 studies to measure the effects of resource booms and anthropogenic disturbance (pastoralism) on diet. We explored whether the probability of prey species occurring in the diet was related to the size of the prey or to prevailing conditions. We also investigated the similarities in diet between dingo populations from across the arid zone, and how dietary overlap was affected by opposing land uses. Dingoes primarily consumed medium‐sized (35–5500 g) and large (>5500 g) mammals, whereas most small mammals (<35 g) were consumed infrequently, or not at all. The composition of the diet changed dramatically during resource booms to exploit irruptive prey species such as long‐haired rats Rattus villosissimus (native; 144 g) and house mice Mus musculus (introduced; 20 g). During resource booms, the consumption of large mammals decreased significantly, whereas the occurrence in the diet of medium‐sized mammals remained high. The diversity of species consumed by dingoes was significantly lower during boom periods than during non‐boom periods. The dingo's heightened consumption of hyper‐abundant species has the potential to release many non‐target species from direct predation pressure during boom times. This could be advantageous for remnant and reintroduced populations of mammals, which are especially susceptible to predation.